2022
DOI: 10.1021/acssuschemeng.2c01194
|View full text |Cite
|
Sign up to set email alerts
|

Microbubble-Assisted Cleaning To Enhance the Removal of Milk Deposits from the Heat Transfer Surface

Abstract: Cleaning is an important unit operation in food processing for removal of fouling deposits to ensure not only optimal operability of process equipment but also product safety and quality. In modern large-scale processing plants, cleaning is commonly achieved by cleaning-in-place (CIP) operation, which, however, consumes large amounts of water, energy, and chemicals. Because of their unique interfacial physicochemical properties, this study incorporated microbubbles (MBs) into water as a novel cleaning agent fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Because the θow reflects the strength of the capillary interaction between the oil droplet and wall, the larger the contact angle, the weaker the interaction; thus, the oil droplet is easier to detach. Previous experimental studies have reported that degreasing with MBs is effective in systems with oleophobic substrates that have large contact angles, such as metal 20,23,26,28,29 and glass surfaces 21,27,30 . Owing to the few studies on oleophilic substrates, the tendency of oil droplet to detach only at the large contact angle of 140° seems reasonable.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the θow reflects the strength of the capillary interaction between the oil droplet and wall, the larger the contact angle, the weaker the interaction; thus, the oil droplet is easier to detach. Previous experimental studies have reported that degreasing with MBs is effective in systems with oleophobic substrates that have large contact angles, such as metal 20,23,26,28,29 and glass surfaces 21,27,30 . Owing to the few studies on oleophilic substrates, the tendency of oil droplet to detach only at the large contact angle of 140° seems reasonable.…”
Section: Resultsmentioning
confidence: 99%
“…MBs is effective in systems with oleophobic substrates that have large contact angles, such as metal 20,23,26,28,29 and glass surfaces. 21,27,30 Owing to the few studies on oleophilic substrates, the tendency of oil droplet to detach only at the large contact angle of 140 seems reasonable.…”
Section: Previous Experimental Studies Have Reported That Degreasing ...mentioning
confidence: 99%
See 1 more Smart Citation
“…MBs have been reported to aid deposit removal by increasing momentum transfer due to bubble scrubbing [42] as well as energy released and shear flow generated by bubble collapse [24]. Moreover, in our previous study on MB-assisted cleaning of fouled heat transfer surface [21], MBs were observed to attach to milk foulant, resulting in enhanced removal. However, the spacer mesh placed to separate the two adjacent membranes and create the feed channel could limit the number of intact bubbles flowing across the spiral membrane, which can explain the insignificant improvement in flux recovery when increasing the bubble density in cleaning liquids.…”
Section: Membrane Cleaningmentioning
confidence: 93%
“…MBs have been applied in various food-related areas, such as increasing soil removal from baby spinach during washing [17], promoting inactivation of Escherichia coli and Salmonella Typhimurium on leafy vegetables [18], enhancing salt diffusion into pork meat during brining [19], and intensifying yeast production [20]. Due to the hydrophobic surfaces, MBs have also proven effective in the cleaning of organic deposits and pollutants, including milk deposit removal from heat transfer surfaces [21], biofilm detachment from the membrane surface [22], food oil deposit removal from the microfiltration membrane [23], fouling reduction on the reverse osmosis membrane [24], and biodiesel removal from sand [25].…”
Section: Introductionmentioning
confidence: 99%